Simulação computacional de tungstatos tipo Scheelita para aplicações ópticas - Amaral, Jomar Batista (2013)
The scheelite type tungstates MWO4 have been studied for a long time due to their optical properties. The main property is the luminescence, both intrinsic and extrinsic (when doped with trivalent lanthanide ions, Ln3+). Another group of scheelite- typed are the double tungstates, ALn(WO4)2. The main feature of these tungstates is a structural disorder involving a random distribution of the ions A (alkali metals) and Ln in the crystal lattice that may influence the luminescence of the material. In literature there are several models to explain both intrinsic and extrinsic luminescence, as recombination of self-trapped excitons, MO and/or WO3 vacancies, stoichiometry deviation, other phases, oxygen at interstitial site, oxygen vacancies and M ion vacancies. As the main technology applications associated with these tungstates are such optics fiber, solid state lasers, scintillators in detectors and recently as white LEDs, it is necessary to better understand and possibly solve or dominate the many physical problems that surround them. Then, using computer simulation based on a model in which the ions are treated as charged spheres interacting through interaction potentials which aim to minimize the lattice energy, tungstates have their perfect and defective crystal lattices simulated to try to elucidate the defect mechanism that dominates and/or contributes for luminescence and its consequences. Using static computer simulation we have as main results: a) 21 different tungstates were modeled using a single set of potential parameters taking into account the covalency of the (WO4)2- group. This covalent interaction affects the behavior of defects, where (WO4)2- groups can be directly connected by an oxygen ion at an interstitial site; b) the charge compensation for extrinsic defects is via interstitial oxygen. When codoped, the codopant ionic radius directly influences the solution energy; c) the simulated energy levels for SrWO4:Eu3+ were compared with recent experimental studies and are in agreement, pointing two different symmetries to the Eu site and d) simulation of holes and electrons in these tungstates reveals that n-type conductivity is expected.